The Influence of Productive Subjects on The Implementation of Practice Internship In Class XI DPIB Islam Vocational School 1 Blitar - Ida Ayu Sulistyoningsih; Isnandar Isnandar; Muhammad Aris Ichwanto; Gulzhaina K Kassymovab (Jurnal Pendidikan Teknik Sipil, 2023)
Background: Prakerin is an implementation of dual-system education by collaboration between the academic and industry sectors. The efficacy of practical internship is contingent upon the acquisition of knowledge, skills, and work attitudes by students during their educational endeavours. Information acquisition is a crucial component for DPIB students, particularly in productive disciplines, as it enables them to apply their learning during internships effectively. This purposes of this research among others: (1) Knowing the mastery of APLPIG subjects in class XI DPIB SMK Islam 1 Blitar. (2) Knowing the mastery of EBK subjects in class XI DPIB SMK Islam 1 Blitar, (3) Knowing the influence of APLPIG subjects on the implementation practical internship, (4) Knowing the influence of EBK subjects on the implementation practical internship and, (5) Knowing the influence of APLPIG and EBK subjects on the implementation practical internship.Methods: The research uses ex-post facto with quantitative method. The process of data collecting involved the utilization of questionnaires as a means of gathering primary data and secondary data was documentationResults: The results show that (1) The level of mastery in APLPIG subjects was 83.3%, (2) The level of mastery in subjects overall was 61.1%, (3) APLPIG subjects had a 28.27% influence on the implementation of practical internship, (4) EBK subjects had a 47.99% influence on the implementation of practical internship, and (5) The combined influence of APLPIG and EBK subjects was 76.3%.Conclusion: This research can be concluded that the productive subjects in the form of APLPIG and EBK subjects' class XI DPIB SMK Islam 1 Blitar will affect the success of the implementation of practice internship carried out. The success is influenced by the mastery of these two subjects which provide provision from the aspect knowledge, skill and work attitudes